Sleep Stage Estimation Comparing Own Past Heartrate or Others' Heartrate. Issue 1 (1st January 2018) - Tajima, Yusuke; Uwano, Fumito; Murata, Akinori; Harada, Tomohiro; Takadama, Keiki
Abstract : To increase the accuracy of real-time sleep stage estimation when only a small number of sleep data can be obtained such as after going to bed, the information for the subject's own sleep and other's past sleep can be used. However, the types of other sleep data such as the subject's own sleep data or other's sleep data, which can contribute to the increase of the sleep stage estimation accuracy, are unknown. Therefore, this paper focuses on these two types of sleep data (i.e., the subject's own sleep data and other's sleep data) and aims to investigate the usefulness of these data for increasing the sleep stage estimation accuracy. Using human subject experiments, the following conclusions have been revealed: (1) the accuracy of the sleep stage estimation is improved using the similarity of either the subject's own past sleep or others' sleep and (2) the accuracy of the estimation method using the sleep data of six other people is higher than those obtained using the data for none, one, or two people.